Assesmen Perkembangan Sosial Emosional Anak Melalui Lembar Kerja Anak di RA Patih Semi Cirebon: Assesmen Perkembangan Sosial Emosional Anak Melalui Lembar Kerja Anak di RA Patih Semi Cirebon - Libri Rizka Puri Windarta (Kindergarten: Jurnal Pendidikan Anak Usia Dini Indonesia, 2023)
Education is an interaction that involves educators, students and materials or teaching materials. The implementation of education is to provide guidance or stimulation through nutrition and behavior to help develop the quality of individuals or groups. The importance of education in supporting the quality of each individual needs to be carried out as early as possible, which is why educational institutions based on early childhood education are present in the midst of society. This study aims to determine the effect of using worksheets on children's social-emotional development. With a qualitative research method that involves collecting data in its implementation, this activity observes how the stimulation of child development through worksheets is planned to develop students' social and emotional development during learning. The results of this study indicate that LKA can affect aspects of child development, in accordance with the development goals studied, namely social- emotional even though it seems monotonous because the questions on the worksheet are too often encountered alias have the same working pattern as worksheets in general.